Quality assurance and measurement in higher education : comparative analysis - Vašenda, Jan; Čadil, Jan; Kotýnková, Magdalena, 1948-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
My dissertation thesis deals with quality assurance and measurement in higher education. In my thesis, the Qualitative comparative analysis (QCA) was used to assess the impact of the accreditation schemes (the main accreditation approach, the involvement of labour market representatives, the possibility of competition of accreditation agencies) and also other relevant features (tuition fees, national language) of the higher education systems of 20 OECD countries on the quality of the higher education sector measured by a world ranking of national higher education systems. The analysis shows that the improvement-oriented accreditation schemes (focused mainly on the internal quality assurance mechanisms and processes) have more positive impact on quality than the ones focused only on the inputs to the learning process. The presence of labour market representatives also proved to have positive effects, though the possibility of competition between accreditation agencies does not. Finally, charging tuition fees seems to result in better quality of higher education. The findings also suggest that English-speaking countries do better in the ranking. The Czech accreditation previously did not focus on internal quality assurance processes and learning outcomes but rather on the quality of inputs into the process of teaching and learning. Empirical evidence shows that the main reasons for not granting accreditation were unsatisfactory credentials of the academic staff and issues related to the proposed programme curriculum. No attention was paid to the process of internal quality assurance and the student learning outcomes. On the contrary, the U.S. accreditation system puts its emphasis on the student learning outcomes and their analysis, which should be monitored by a well-functioning internal quality assurance system. The former accreditation system used in the Czech Republic did not have a positive impact on the higher education sector.
t is still too early for any comprehensive analysis of the new accreditation scheme. The most important question to answer is what will be the main criterion for (not) granting the accreditation exercised by the accreditation officials, and whether we will really shift to a different model of accreditation. The long-term review of the decisions made by the National Accreditation Bureau will certainly be the subject of my future research.
Vedoucí práce: Jan Čadil
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: hospodářská politika [obor disert. práce]; disertace; dissertations